Studing Of Some Phisical Properties And Morphology Of Blends Of Hdpe /Lldpe After And Before Exposure To Uv Light - Najat J. Saleh; Nabeela A. Mohammed; Weam A. Abed (Engineering and Technology Journal, 2009)
Products made of polyethylene used out doors are subjected to UV-degradation. Infact, many polymers show changes in physical properties during service lifetime, whenthey are exposed to sun light and particularity to UV-light. In the present work, thephysical properties and the morphology of blends of high – density polyethylene(HDPE)/linear-low-density polyethylene (LLDPE) studied before and after exposure toUV –light.HDPE was mixed with different weight percent (0, 15, 30, and 45%) of LLDPE usingthe two roll mills; the mixing machine is operated at a temperature of 135 oC.Weathering test was carried out to find the effect of the environment condition on thephysical properties of the polymeric materials by increasing the exposure times to(100,200,300) hr. The physical properties and the morphology were specified bymeasuring the (absorption properties, and densities), for the former, andphotomicrograph for the latter. The results obtained in this work show that the density ofpure HDPE and HDPE/LLDPE blends increased with the increasing the exposure time,and that immersing the HDPE and HDPE/LLDPE blends in water can produce a varietyof damage and this damage increased with the increasing of the exposure times also, asthe amount of LLDPE is increased in the HDPE/LLDPE blends the amount of waterabsorbed and diffusivity coefficient, increase greatly, and from the optical micrographresults showed clearly the damage obtained due to exposure to UV light for 300 hr forpure HDPE and HDPE/LLDPE blends.